2019
DOI: 10.1016/j.fertnstert.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of anxiety and depression among Chinese women transitioning through menopause: findings from a prospective community-based cohort study

Abstract: Objective: To determine the prevalence of symptoms of anxiety and depression in Chinese women during and after menopause, and the associated risk factors. Design: Prospective community-based cohort study. Setting: An urban community in Beijing, People's Republic of China. Patient(s): Four hundred and thirty women who had transitioned through natural menopause. Intervention(s): None. Main Outcome Measure(s): Symptoms of anxiety and depression. Result(s): Symptoms of depression were more common than symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 48 publications
2
51
0
1
Order By: Relevance
“…An increased risk of depression during the menopause transition has been previously observed [ 18 , 19 , 20 ]. In a Chinese study based on a group of 430 women from urban areas, almost 20% of postmenopausal women had symptoms of depression, compared to 14.5% of premenopausal women [ 21 ]. Additionally, the independent predictors for symptoms of depression were as follows: higher body mass index, poor health, low education status, and night sweats [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased risk of depression during the menopause transition has been previously observed [ 18 , 19 , 20 ]. In a Chinese study based on a group of 430 women from urban areas, almost 20% of postmenopausal women had symptoms of depression, compared to 14.5% of premenopausal women [ 21 ]. Additionally, the independent predictors for symptoms of depression were as follows: higher body mass index, poor health, low education status, and night sweats [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Chinese study based on a group of 430 women from urban areas, almost 20% of postmenopausal women had symptoms of depression, compared to 14.5% of premenopausal women [ 21 ]. Additionally, the independent predictors for symptoms of depression were as follows: higher body mass index, poor health, low education status, and night sweats [ 21 ]. A study based on Arab women also reported a greater prevalence of depression and anxiety in postmenopausal women compared to menopausal ones [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To make matters worse, since the average age of female in this study was 57.90 ± 9.89, female patients also faced an increased risk of postmenopausal depression. According to the study of menopausal depression symptoms among Chinese women, postmenopausal (56.6 ± 4.9) depression rates were higher than premenopausal (45.3 ± 3.2) and menopausal (48.6 ± 3.4) depression (57).…”
Section: Discussionmentioning
confidence: 98%
“…In women during the menstrual transition both symptoms such as depression and anxiety are shown to be more common in some studies, and these symptoms both depression and anxiety are less in men when compared with women and said to be about twice prevalent in women. Variance in the risk of the depression and anxiety is by difference in race with few social and demographic factors (including socioeconomic status and level of education) and is considered as another important issue that requires attention [33].…”
Section: Psychological Symptomsmentioning
confidence: 99%